Controlled morphology evolution of electrospun carbon nanofiber templated tungsten disulfide nanostructures. (10th September 2015) - Zou, Meiling; Jiang, Ying; Wan, Meng; Zhang, Ming; Zhu, Han; Yang, Tingting; Du, Mingliang
Abstract: Three-dimensional (3D) WS2 -nanoflower decorated and two-dimensional (2D) WS2 -nanosheet (NS) wrapped carbon nanofiber (CNF) nanostructures are constructed through a simple approach using (NH4 )2 WS4 contained electrospun polyacrylonitrile nanofibers (W-PAN NFs) and S powder as the precursor. (NH4 )2 WS4 are thermally decomposed into WS2 nanoparticles (NPs) during a pre-oxidation treatment of W-PAN NFs. Interestingly, the introducing of S vapor during the carbonization of W-PAN NFs results in unexpected migration of WS2 nanoparticles (WS2 NPs) from the inside of CNFs to the surface to form WS2 NSs or WS2 nanoflowers. It is believed that S not only controls the initial nucleation of WS2 on the surface of CNFs but also induces the migration of WS2 NPs and directs the growth of WS2 into various morphologies. The synthesized catalysts are directly used as the electrode for hydrogen evolution reaction (HER) and they exhibit good electrocatalytic activity.